The role of immune activation and antigen persistence in acute and long COVID. (June 2023) - Opsteen, Skye; Files, Jacob K; Fram, Tim; Erdmann, Nathan
In late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) triggered the global coronavirus disease 2019 (COVID-19) pandemic. Although most infections cause a self-limited syndrome comparable to other upper respiratory viral pathogens, a portion of individuals develop severe illness leading to substantial morbidity and mortality. Furthermore, an estimated 10%–20% of SARS-CoV-2 infections are followed by post-acute sequelae of COVID-19 (PASC), or long COVID. Long COVID is associated with a wide variety of clinical manifestations including cardiopulmonary complications, persistent fatigue, and neurocognitive dysfunction. Severe acute COVID-19 is associated with hyperactivation and increased inflammation, which may be an underlying cause of long COVID in a subset of individuals. However, the immunologic mechanisms driving long COVID development are still under investigation. Early in the pandemic, our group and others observed immune dysregulation persisted into convalescence after acute COVID-19. We subsequently observed persistent immune dysregulation in a cohort of individuals experiencing long COVID. We demonstrated increased SARS-CoV-2-specific CD4 + and CD8 + T-cell responses and antibody affinity in patients experiencing long COVID symptoms. These data suggest a portion of long COVID symptoms may be due to chronic immune activation and the presence of persistent SARS-CoV-2 antigen. This review summarizes the COVID-19 literature to date detailing acute COVID-19 and convalescence and how these observations relate to the development of long COVID. In addition, we discuss recent findings in support of persistent antigen and the evidence that this phenomenon contributes to local and systemic inflammation and the heterogeneous nature of clinical manifestations seen in long COVID.